Effect of laser parameters and shielding gas flow on co-axial photodiode-based melt pool monitoring signals in laser powder bed fusion - Reijonen, Joni (Elsevier B.V., 2025)
Melt pool monitoring using co-axial photodiodes is increasingly used for online quality monitoring in PBF-LB AM. However, the fundamental correlations between different processing conditions and the co-axial photodiode signals are not well understood. In this study the impact of laser parameters and the shielding gas flow speed on co-axial photodiode-based melt pool monitoring signals is established. It is shown that laser power has positive linear correlation with the photodiode signal, while the correlation with scanning speed is non-linear in the form of y=ax–b. The focal point position, scanning orientation and shielding gas flow speed have highly non-linear response on the photodiode signal, depending on the combinatorial effects of the parameters. These underlying physical correlations should be carefully assessed and taken into consideration when trying to establish correlations between photodiode-based melt pool monitoring signal and defect formation in the PBF-LB process.